Hygiene practices and factors influencing intestinal parasites among food handlers in the province of Belgarn, Saudi Arabia - Alqarni,Abdulrahman S.; Wakid,Majed H.; Gattan,Hattan S. (PeerJ, 2023)
Background This study aimed to evaluate the association between socio-demographic status, and hygienic habits among food handlers with intestinal parasitic infections. Methods It was a cross-sectional study in which 112 participants were recruited, from Belgarn province of Saudi Arabia. The descriptive analysis was used to evaluate demographic data and categorical variables. The association between sociodemographic characteristics and Relative Risk regression analysis was performed for each investigated factor. p-value of <0.05, was assumed to be statistically significant. Results One hundred and twelve food handlers with a mean age of 33.5 ± 9.2 years were included in this study. The food handlers were from 15 different countries (11 Asians and four Africans). The majority of the food handlers were cooks (87, 77.7%), and waiters and dish washers (24, 21.4%). Among them, 106 (94.6%) used uniforms, and gloves at work. In hand washing practices, 104 (92.9%) wash their hands with soap before handling and preparing food and eight (7.1%) wash without soap, 98 (87.5%) wash with soap before meals and 14 (12.5%) wash without soap, 105 (93.8%) wash with soap after visiting toilets and seven (6.2%) wash without soap. Twenty-five (42.3%) of infected food handlers are not used to trim their fingernails. Intestinal infection was observed in 59 (52.68%) participants with mean age (32.5 ± 8.1 years) for infected participants. Conclusion In this study, food handlers had a high prevalence of intestinal parasites. Although some of the food handlers had a high level of education, the infection with intestinal parasites was detected. In addition to regular screening for intestinal parasites among food handlers, there is a need for educational programs on proper hygiene habits, modes of transmission and prevention of the infection.
Keywords: Hygiene practices; Intestinal parasites; Food handlers; Socio-demographic status; Risk factors; Belgarn; Saudi Arabia